Effect of the Seasonal Changes on Renal Function in Patients with Acute Ischemic Stroke - Güleser Akpınar; Mustafa Boğan; Kaan Yusufoğlu; Miray Korkmaz; Emine Gül Baldane; Erdem Çevik (Bagcilar Medical Bulletin, 2020)

(untitled)
Objective:This study aimed to define seasonality trends of acute renal dysfunction in the patients with ischemic stroke.Method:This study was conducted retrospectively. Data were obtained from digital records of Şişli Hamidiye Etfal Training and Research Emergency Medicine Clinical Statistic Office.Results:One hundred ninety-nine patients with ischemic stroke were included in the study. Patients were divided into two groups according to their renal functions. Group 1 (patients with abnormal renal function) included 70 patients. In this group, the mean urea value was 67.3±26.9 mg/dL, the mean creatinine value was 1.4±1.1 mg/dL, the mean age was 77.0±6.5 years, 34 patients were male (48.6%). Group 2 (patients with normal renal function) included 129 patients. In this group, the mean urea value was 37.9±9.9 mg/dL, the mean creatinine value was 0.9±0.2 mg/dL, the mean age was 76.6±7.3 years, 74 patients were male (57.4%). Season distribution, age and gender distribution, affected area of the brain, and platelet count did not show significant differences between the groups (p>0.05).Conclusion:There is not a significant relationship between seasonal changes and renal dysfunction in the patients with ischemic stroke.